Treating the Deviated or Wide Nasal Dorsum - Davis, Richard E.; Foulad, Allen I. (Facial Plastic Surgery, 2017)
Both deviation and excessive width of the nasal dorsum result in conspicuous facial disharmony and are often attended by nasal airway dysfunction. Whether the result of developmental growth disturbances, nasal trauma, failed nasal surgery, or combinations therein, deviation and splaying of the nasal dorsum can be exceedingly difficult to treat. Individualized treatment is paramount because contour variations are seemingly endless, and a careful preoperative assessment of the anatomic, physiologic, cosmetic, and psychosocial factors that characterize the deformity is necessary to devise an effective patient-specific treatment plan. Ensuring the linearity, strength, alignment, and aesthetically pleasing profile dimensions of the nasal L-strut is the requisite first step in successful treatment. Releasing all deformed components in a controlled and precise manner using powered instrumentation (whenever possible) to facilitate minimally traumatic and effective repositioning, followed by structural reconstitution of the skeletal framework using autologous graft materials, and then consolidation of the newly created construct with suture fixation completes the transformation to normalcy. Paying equal attention to both cosmetic and functional wellness, while simultaneously seeking to maximize structural stability, serves to optimize the final outcome.
Keywords: deviated dorsum; wide dorsum; L-strut; nasal axis; dorsal aesthetic lines